Heterogeneity in risk‐sensitive allocation of somatic reserves in a long‐lived mammal. Issue 7 (12th July 2022) - Smiley, Rachel A.; Wagler, Brittany L.; LaSharr, Tayler N.; Denryter, Kristin A.; Stephenson, Thomas R.; Courtemanch, Alyson B.; Mong, Tony W.; Lutz, Daryl; McWhirter, Doug; Brimeyer, Doug; Hnilicka, Patrick; Lowrey, Blake; et al.
Abstract: Food quality and availability, when combined with energetic demands in seasonal environments, shape resource acquisition and allocation by animals and hold consequences for life‐history strategies. In long‐lived species with extensive maternal care, regulation of somatic reserves of energy and protein can occur in a risk‐sensitive manner, wherein resources are preferentially allocated to support survival at the cost of investment in reproduction. We investigated how Rocky Mountain bighorn sheep ( Ovis canadensis ), an alpine mammal in a highly seasonal environment, allocates somatic reserves across seasons. In accordance with the hypothesis of risk‐sensitive resource allocation, we expected accretion and catabolism of somatic reserves to be regulated relative to preseason nutritional state, reproductive state, and variation among populations in accordance with local environmental conditions. To test that hypothesis, we monitored seasonal changes in percent ingesta‐free body fat (IFBFat) and ingesta‐free, fat‐free body mass (IFFFBMass) in three populations of bighorn sheep in northwest Wyoming between 2015 and 2019 through repeated captures of female sheep in December and March of each year in a longitudinal study design. Regulation of somatic reserves was risk‐sensitive and varied relative to the amount of somatic reserves an animal had at the beginning of the season. Regulation of fat reserves was sensitive to reproductive state and differed by population, particularly over the summer. In one population with low rates of recruitment of young, sheep that recruited offspring lost fat over the summer in contrast to the other two populations where sheep that recruited gained fat. And yet, all populations exhibited similar changes in fat catabolism and risk sensitivity over winter. The magnitude of body fat and mass change across seasons may be indicative of sufficiency of seasonal ranges to meet energetic demands of survival and reproduction. Risk‐sensitive allocation of resources was pervasive, suggesting nutritional underpinnings are foundational to behavior, vital rates, and, ultimately, population dynamics. For species living in alpine environments, risk‐sensitive resource allocation may be essential to balance investment in reproduction with ensuring survival.